Effect of black soybean flour particle size on the nutritional, texture and physicochemical characteristics of cookies. (15th July 2022) - Yang, Liping; Wang, Sunyan; Zhang, Wangfen; Zhang, Houfang; Guo, Li; Zheng, Shulin; Du, Chuanlai
Abstract: In order to enrich the cookies' nutrition, black soybean was used to develop cookies, and the effect of its particle size on the characteristics of cookies was analysed. The results showed that the chemical score of black soybean cookies (12.02–13.24) was significantly greater than that of wheat flour cookies (9.14), which was significant for improving cookies' nutrition. The cookies thickness decreased when the particle size of black soybean flour decreased, but the spread ratio increased. The addition of black soybean flour greatly decreased the lightness of the cookie from 74.79 to 51.32. The decrease in particle size affected texture of cookies, especially for hardness and fracturability, they increased from 12.22 to 13.86 N, and decreased from 1.26 to 1.02 g, respectively. The addition of black soybean remarkably increased the slowly digestible and resistant starch, especially for cookies made from coarse black soybean flour, up to 50.22% and 26.10%, respectively. The black soybean flour enhanced the binding force of free water in cookies system, giving cookies a higher crispness. Based on physicochemical properties and nutrition analysis, using black soybean flour to develop cookies is feasible in industrial practice. And from sensory analysis, superfine black soybean flour was preferred for cookies production. Highlights: Black soybean powders of five different particles sizes were prepared. The effect of particle size on the characteristics of cookies was studied. From nutritional analysis, coarse black soybean powder was more proper for cookie. Texture analysis showed fine black soybean cookies were preferred.